2017
DOI: 10.1128/iai.01020-16
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Neutrophils Mediated by Vγ2 γδ T Cells Deteriorates Liver Fibrosis Induced by Schistosoma japonicum Infection in C57BL/6 Mice

Abstract: Conventional adaptive T cell responses contribute to the pathogenesis of Schistosoma japonicum infection, leading to liver fibrosis. However, the role of gamma-delta (γδ) T cells in this disease is less clear. γδ T cells are known to secrete interleukin-17 (IL-17) in response to infection, exerting either protective or pathogenic functions. In the present study, mice infected with S. japonicum are used to characterize the role of γδ T cells. Combined with the infection of S. japonicum, an extremely significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
(59 reference statements)
5
29
2
Order By: Relevance
“…However, an earlier study investigating the relative roles of αβ and γδ T cells in the immunopathology of schistosomiasis found that mutant mice lacking γδ T cells display vigorous formation of egg granulomas similar to normal mice, which demonstrates that granuloma formation is not dependent on γδT cells (127). In contrast with this study, another study identified two different γδ T cell subsets, including the Vγ1 γδ T cells that secrete IFN-γ only and the Vγ2 γδ T cells that secrete both IL-17A and IFN-γ (74). During S. japonicum infection, Vγ2 γδ T cells prevent hepatic fibrosis by recruiting neutrophils and secreting IL-17A (74).…”
Section: Innate γδ T Cells In Schistosomiasiscontrasting
confidence: 72%
See 2 more Smart Citations
“…However, an earlier study investigating the relative roles of αβ and γδ T cells in the immunopathology of schistosomiasis found that mutant mice lacking γδ T cells display vigorous formation of egg granulomas similar to normal mice, which demonstrates that granuloma formation is not dependent on γδT cells (127). In contrast with this study, another study identified two different γδ T cell subsets, including the Vγ1 γδ T cells that secrete IFN-γ only and the Vγ2 γδ T cells that secrete both IL-17A and IFN-γ (74). During S. japonicum infection, Vγ2 γδ T cells prevent hepatic fibrosis by recruiting neutrophils and secreting IL-17A (74).…”
Section: Innate γδ T Cells In Schistosomiasiscontrasting
confidence: 72%
“…In contrast with this study, another study identified two different γδ T cell subsets, including the Vγ1 γδ T cells that secrete IFN-γ only and the Vγ2 γδ T cells that secrete both IL-17A and IFN-γ (74). During S. japonicum infection, Vγ2 γδ T cells prevent hepatic fibrosis by recruiting neutrophils and secreting IL-17A (74). Thus, the role of innate γδ T cells in the pathology of schistosomiasis requires further investigation.…”
Section: Innate γδ T Cells In Schistosomiasiscontrasting
confidence: 56%
See 1 more Smart Citation
“…Leishmania and Toxoplasma gondii also induce expression of IL‐17A, the role of which is still unclear because both protective and non‐protective roles have been reported. Schistosoma helminths, which cause liver granulomas and fibrosis, also induce IL‐17A production by Th17 and γδ T cells . Lack of IL‐17A or IL‐23 results in decreased granuloma formation and suppression of liver fibrosis, indicating that IL‐17A can exacerbate clinical symptoms of schistosomiasis.…”
Section: Role Of Hematopoietic Cell‐derived Il‐17a In Infectionsmentioning
confidence: 99%
“…Hepatic γδ T cells are often Vγ4 cells and secrete the cytokine IL-17 and/or IL-10 [13]. Studies in mice indicate a role for IL-17 producing γδ T cells in liver fibrosis and immune pathology during infection with Schistosoma japonicum [14][15][16][17] and SM [18]. They can either be pathogenic as in the case of S. japonicum, or protective in the case of Listeria monocytogenes [13].…”
Section: Introductionmentioning
confidence: 99%